2020
DOI: 10.1176/appi.focus.18102
|View full text |Cite
|
Sign up to set email alerts
|

Community Interventions to Promote Mental Health and Social Equity

Abstract: We review recent community interventions to promote mental health and social equity. We define community interventions as those that involve multi-sector partnerships, emphasize community members as integral to the intervention, and/or deliver services in community settings. We examine literature in seven topic areas: collaborative care, early psychosis, school-based interventions, homelessness, criminal justice, global mental health, and mental health promotion/prevention. We adapt the social-ecological model… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 109 publications
0
16
0
1
Order By: Relevance
“…These multi-level influences may dynamically interact, interrelate or be interdependent across different levels so that the model functions as a whole system. This model explains the interactive relationships between individuals and environments (26,27). During the COVID-19 pandemic, it has been widely applied to examine multilevel factors influencing COVID-19 preventive Costs and profits † Feed and petrol †…”
Section: Figurementioning
confidence: 99%
“…These multi-level influences may dynamically interact, interrelate or be interdependent across different levels so that the model functions as a whole system. This model explains the interactive relationships between individuals and environments (26,27). During the COVID-19 pandemic, it has been widely applied to examine multilevel factors influencing COVID-19 preventive Costs and profits † Feed and petrol †…”
Section: Figurementioning
confidence: 99%
“…Van Citters and Bartels in their review found that home and community-based treatment of older adult psychiatric patients were associated with improved and longer maintained psychiatric status [32]. Finally, in a recent study, Castillo et al (2019) demonstrated the effectiveness of community interventions for improving mental health [33].…”
Section: Discussionmentioning
confidence: 99%
“…As principais informações sobre o caso clínico e também as características do paciente são indicadas no cenário. Todas as informações devem estar relacionadas aos objetivos propostos para a atividade, sendo interessante o compartilhamento das metas do Exame Clínico Objetivo Estruturado com a atriz simulada (25) . Nesse cenário, também foram abordadas pistas necessárias para a ação e pistas que podem ser utilizadas para colaborar com a compreensão e abordagem da atriz simulada com a realidade do tema.…”
Section: Discussionunclassified